Plasticity of Mature B Cells Between Follicular and Classic Hodgkin Lymphomas: A Series of 22 Cases Expanding the Spectrum of Transdifferentiation. (January 2022) - Trecourt, Alexis; Mauduit, Claire; Szablewski, Vanessa; Fontaine, Juliette; Balme, Brigitte; Donzel, Marie; Laurent, Camille; Sesques, Pierre; Ghesquières, Hervé; Bachy, Emmanuel; Salles, Gilles; Emile, Jean-François; et al.
Abstract : Follicular lymphoma and classic Hodgkin lymphoma can be associated in composite and/or sequential lymphomas. Common IGH and BCL2 rearrangements have already been identified between both contingents of these entities, but mutation profiles have not yet been investigated. The main objective of this study was to analyze the transdifferentiation process that may occur between Hodgkin and follicular contingents in sequential and composite lymphomas to better characterize these entities. From 2004 to 2020, a retrospective multicentric study was performed, including 9 composite and 13 sequential lymphomas. Clinical data were retrospectively collected. Fluorescent in situ hybridization of BCL2 and BCL6 rearrangements, polymerase chain reaction of IGH and IGK rearrangements, next-generation sequencing of IGK rearrangement, and targeted next-generation sequencing (TNGS) on a panel of genes frequently mutated in lymphomas were performed on each contingent of composite and sequential lymphomas. For TNGS, each contingent was isolated by laser capture microdissection. Clinical presentation and evolution were more aggressive in sequential than composite lymphomas. By fluorescent in situ hybridization, common rearrangements of BCL6 and BCL2 were identified between both contingents. Similarly, a common clonal relationship was established by evaluating IGH and IGK rearrangement by polymerase chain reaction or next-generation sequencing. By TNGS, the same pathogenic variants were identified in both contingents in the following genes: CREBBP, KMT2D, BCL2, EP300, SF3B1, SOCS1, ARID1A, and BCOR . Specific pathogenic variants for each contingent were also identified: XPO1 for Hodgkin lymphoma contingent and FOXO1, TNFRSF14 for follicular lymphoma contingent. This study reinforces the hypothesis of a transdifferentiation process between Hodgkin and follicular contingent of sequential/composite lymphomas. Abstract : Supplemental Digital Content is available in the text.